Selective anti-cancer effects of cannabidiol and Δ9-tetrahydrocannabinol via PI3K/AKT/mTOR inhibition and PTEN restoration in ovarian cancer cells - Tong, Siyao; Loilome, Watcharin; Namwat, Nisana; Klanrit, Poramate; Wangwiwatsin, Arporn; Win, Zar Zar; Koyabuth, Preeya; Chumworathayi, Bandit (Frontiers in Pharmacology, 2025)
IntroductionOvarian cancer is a highly lethal gynecological malignancy, often diagnosed at advanced stages. Cannabidiol (CBD) and delta-9-tetrahydrocannabinol (THC) demonstrate anti-tumor activity in various cancers including ovarian cancer through multiple signaling pathways and are increasingly explored as adjuncts to chemotherapy. However, the effects of CBD and THC combination treatment and its specific mechanisms remain unclear. This study evaluated the anti-tumor effects of CBD, THC, and their combination on SKOV3 and A2780 ovarian cancer cells, focusing on phosphorylation-dependent regulation of the PI3K/AKT/mTOR pathway.MethodsSKOV3, A2780, and IOSE cells were treated with CBD, THC, and equimolar CBD: THC combinations. Cytotoxicity was assessed using Sulforhodamine B assay, while synergistic interactions were analyzed by the Chou-Talay method using CompuSyn. Cell cycle distribution and apoptosis were evaluated, and phosphorylation of PI3K, AKT, mTOR, and PTEN was examined by Western blotting.ResultsThe CBD: THC combination treatment showed potent, selective cytotoxicity at 48 h, with lower IC50 values than in non-tumor IOSE80 cells. The Chou–Talalay method validated a synergistic effect between CBD and THC. The combination treatment induced cell cycle arrest and enhanced apoptosis. Western blot analysis exhibited that equimolar CBD: THC (2.5:2.5 μM) markedly reduced phosphorylation of PI3K, AKT, and mTOR, while increasing phosphorylation of PTEN, thereby reactivating tumor-suppressive signaling.ConclusionThese findings highlight that CBD: THC combination treatment effectively inhibited ovarian cancer cell growth and invasion via oncogenic PI3K/AKT/mTOR signaling and reactivates PTEN. The combination may represent a promising targeted therapeutic approach, warranting further in vivo validation to elucidate its clinical potential.